The Relationship of Nurses' Caring Attitudes with Patient Satisfaction in the Operating Room and Internal Room of Toto Kabila Hospital - Nurfadillah Hamzah; Sabirin B. Syukur; Euis Herawati Hidayat (Universitas Muhammadiyah Palu, 2026)
Caring attitude is the core of nursing practice which plays an important role in improving the quality of service and patient satisfaction. Patient satisfaction is an important indicator in assessing the quality of health services in hospitals. The caring behavior shown by the nurse can affect the patient's perception of the services received during the treatment process. This study aims to determine the relationship between nurses' caring attitudes and patient satisfaction in the Operating Room and Internal Room of Toto Kabila Hospital. This study uses a quantitative method with a cross sectional design. The sample in this study amounted to 94 respondents who were selected using the purposive sampling technique. Data collection was carried out using a nurse caring attitude questionnaire and a patient satisfaction questionnaire. The results showed that most of the respondents assessed the caring attitude of nurses to be in the category of caring enough as many as 59 respondents (62.8%), the caring category as many as 23 respondents (24.5%), and the less caring category as many as 12 respondents (12.8%). The level of patient satisfaction was mostly in the category of satisfied as many as 63 respondents (67.0%), the satisfied category as many as 21 respondents (22.3%), and the dissatisfied category as many as 10 respondents (10.6%). The results of the Chi-square test showed a value of p = 0.002 (p < 0.05) which means that there is a significant relationship between the caring attitude of nurses and patient satisfaction in the Operating Room and Internal Room of Toto Kabila Hospital. This study concluded that the better the caring attitude of nurses, the higher the level of patient satisfaction with the nursing services received.